Desarrollo psicomotor y autoestima en los niños de 7mo de Educación Básica paralelo “A” de la Escuela de Educación Básica “Fe y Alegría” de la ciudad de Riobamba. En el periodo lectivo 2023 - 2024 - Berrones Carrasco, Dayana Nicole (2024)
The main objective of this research study was to determine the influence of psychomotor development on the self-esteem of children in the 7th grade of Educación General Básica de la Escuela de Educación Básica "Fe y Alegría" in the city of Riobamba because psychomotor development is of great importance for the acquisition of skills such as speaking, walking, writing, among others, which provides a good performance in all areas where the individual is; but self-esteem should also be considered as the basis of selfesteem, personal conceptions, feeling fit to carry out activities and being accepted in society. In turn to these variables, strategies are proposed for the development of each one of them. The methodology used was of a qualitative and quantitative approach; qualitative because it is related to the Sciences of Education and human behavior, and quantitative because evaluation techniques and instruments were proposed; as a first instance to the teachers of the Educational Institution a questionnaire of ten questions, related to the psychomotor development and self-esteem of the students, in addition from this instrument it was also possible to know if the teachers applied strategies for the development of the variables proposed. Subsequently, the Rossemberg scale, consisting of ten questions focused on self-esteem, with four response alternatives, was applied to the students of 7th grade EGB, parallel "A". The data obtained from the instruments were processed using the Microsoft Excel package, where a low percentage reached high selfesteem, which is worrying for their integral formation.